Unnatural (2018), volume 3 ebook Rebirth. - Andolfo, Mirka (Unnatural (2018), 2019)
This final chapter of the hit comic, an acclaimed fantasy, erotica, romantic suspense series by MIRKA ANDOLFO (Wonder Woman, Harley Quinn, DC Comics Bombshells), has still more surprises in store, between breathtaking twists and exciting developments! Newspapers call her a killer, her allies are dead or beaten to a pulp, and her enemies are closing in on her. Oh, and she still has a major "inner demons" problem to face. So let's agree that things have gotten pretty serious. Will Leslie be strong enough to survive all this, or is this really the end of the line for her? Collects UNNATURAL #9-12. Author: Mirka Andolfo. Illustrator: Mirka Andolfo . 2019 Mirka Andolfo.